Pérdida familiar y su incidencia en los estados depresivos de una adolescente de 15 años de la ciudad de Babahoyo - Narvaez Alcivar, Daniela Yamilet (2022)
The present case study referring to family loss and its incidence in the depressive state of a 15-year-old adolescent in the city of Babahoyo, describes in detail how the death of a loved one affects the emotional area, taking into account that the process of Overcoming grief will depend on the causes of the death, the affective bond and the strength to assimilate the pain, since the loss of a loved one causes different emotions that directly interfere with the quality of life and the usual performance of the activities of any human being. In order to satisfactorily complete the proposed investigation and gather all the pertinent information that helped to know the degree of affectation caused by the family loss in the emotional state of the young woman, it was necessary to apply different investigative methods such as direct observation, semi-structured interviews, elaboration of history clinic, and the application of psychometric tests that served as support to evaluate the patient and learn more about her symptoms, thoughts, emotions and behavior for which it was essential to follow a procedure to establish the appropriate psychological diagnosis and determine that it is important to always take care mental health, because the consequences can be negative, ending in serious states of depression that harm people's affective state and their relationships with their friends and family, preventing their daily lives from developing normally, and although it is true that not all grieving process or it requires the participation of a professional because most people will get over it as time goes by, if it is advisable to seek psychological help when the problem gets out of hand and it is difficult to overcome it.